في تحليل العوامل المؤثرة على مرض القلب Cluster Analysis استخدام التحليل العنقودي - حميد, سميرة مزهر; عباس, تهاني مهدي; نايف, قتيبة نبيل (Al-Nahrain Journal of Science, 2010)
This research aims to study the heartdisease and the factors which are cause it, andclassify these factors into different groupsaccording to its similarity degree by usingcluster analysis which is consider theimportant statistical ways which have manyuses, e.g. data classification (variables orobservations).This way was applied on sample contain630 heart patients; four ways of cauterizingwere applied by using the program (Minitab).After results analysis we find that three ofthese ways show the same results accordingclustering variables which are collecting inthree clusters according to similarity degree